Evolution of cryogenics – A review on applications of cryogenics in medicine. (2021) - Jain, Pratyush; Agarwal, Prafull; Mathur, Dhruv; Singh, Praneet; Sharma, Ashish
Abstract: Cryogenics is that discipline of engineering, which studies the behaviour of materials and their properties at shallow temperatures. The ultra-low temperatures change the chemical attributes which open a gateway for new applications of materials. These studies have not only contributed to the invention of different materials but has also laid a foundation for future technologies. Using cryogenic sciences, we can achieve new milestones in medicine and human-life expectancy can be significantly increased. Since ancient times, applications of cryogenic temperatures were implemented for medical treatment. Cryotherapy is one of the oldest methods known to heal wounds and relieve pain. Today, cryogenic freezing is being practiced to store blood and human organs for prolonged periods. Even surgical extermination of lethal tissues & viruses is being laid out using the principles of cryogenic freezing. This paper discusses the history of cryogenics and its advancements in the field of medical science.